Hrvatski sveučilišni športski savez - HSŠS - Gošnik, Jelka (2005)
This paper gives information on CUSF membership, its constitution, aims and activities, CUSF cooperation, material and finance management, accomplished tasks in 2004 and tasks planned for 2005.